2019
DOI: 10.2217/pmt-2018-0076
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Prescription of Opioids Among Prostate Cancer Patients of Various Racial Groups

Abstract: Aim: To examine disparities in opioid prescription between different races of prostate cancer patients. Materials & methods: We used the Medical Expenditure Panel Survey data (2013–2015) and developed a model based on covariates that may affect opioid prescription and based on this model, we carried out logistic regression, where our outcome of interest was prescription of at least one opioid among prostate cancer patients. Results: Compared with non-Hispanic whites, Hispanics had 0.490 (0.214–1.123), non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 5 publications
0
3
1
Order By: Relevance
“…35 It is possible that providers perceive patients as overstating their pain, but this perception is tempered by a life-threatening diagnosis such as cancer. 21 Our study found no difference in opioid prescriptions between visits by male and female patients with pancreatitis or pancreatic cancer. This finding is inconsistent with overall trends toward higher rates of opioid prescriptions for adult female patients compared with male patients in the United States.…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations
“…35 It is possible that providers perceive patients as overstating their pain, but this perception is tempered by a life-threatening diagnosis such as cancer. 21 Our study found no difference in opioid prescriptions between visits by male and female patients with pancreatitis or pancreatic cancer. This finding is inconsistent with overall trends toward higher rates of opioid prescriptions for adult female patients compared with male patients in the United States.…”
Section: Discussioncontrasting
confidence: 57%
“…A 2019 Medical Expenditure Panel Survey-based study similarly concluded that there were no significant differences in opioid prescriptions between Hispanic and non-Hispanic prostate cancer patients. 21 Another study of breast cancer patients found no disparity in opioid prescriptions for Blacks and Whites; however, as the authors note, this finding does not imply that they have their analgesic needs equally met. 22 There are several possible reasons for disparities in opioid prescriptions between Hispanic and non-Hispanic patients with benign disease that seem to dissipate in malignant disease.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations